(untitled) (Journal of Economic Research & Business Administration, 2019)
The article discusses the concept of «super-flexibility» and principles of super-flexible companies studied by H. Bahrami and S. Evans during their work in the Silicon Valley. Considering the pace and trends of Kazakhstan’s business transformation the authors of the article have concluded that the principles and models of super-flexible organizational structures can become a methodological basis for managing companies in Kazakhstan and that would increase the country’s competitiveness in the future. Companies that adhere to the principles of super-flexible companies will have the ability to quickly and effectively respond to the situation as well as be able to resist the pressure from the external environment. Based on the researches of H. Bakhromi and S. Evans on superflexible companies, questionnaires were compiled and the first executives of the companies were interviewed, were revealed the prerequisites and necessity of forming superflexible companies in Kazakhstan. The authors concluded that if managers of companies in Kazakhstan will use the principles of super-flexible companies, they will be able to respond quickly to changes and will be able to take leading positions on the market.